Electrostatically and Electrodynamically Stimulated Ca and Zr- doped MgSiO3 [Mg1-xCaxSi1-xZrxO3 (x = 0 - 0.4), MCSZO] Bioceramics for Orthopedic Implant Application. - Singh, Priya (IIT(BHU) Varanasi, 2024)
Abstract is available in the attachment.
Keywords: Ceramic Engineering